Investigating the use of oligonucleotides for the treatment of muscular dystrophy - Moore, Rebecca L. L. (2016)
Antisense oligonucleotide therapy is one of the most promising strategies for treatment of myotonic dystrophy type 1 (DM1), type 2 (DM2) and Duchene muscular dystrophy (DMD). These three diseases have nuclear retained mRNA, suitable for antisense therapy targeting. The delivery of oligonucleotides to their desired target has long been an obstacle in antisense therapy with a large number of delivery reagents or methods having adverse side effects. Promising work published detailing the successful delivery of various chemically modified oligonucleotides (CMOs) naked, via gymnosis, led to us investigating a number of these CMOs: deoxyribonucleic acids (DNA), Peptide nucleic acids (PNAs), 2’OMethyl (2’OMe), and Phosphorodiamidate morpholino (PMO) oligonucleotides. In DM1 expanded CUG repeat (CUGexp) mRNAs aggregate in the nucleus forming “foci”. Testing the CMOs effectiveness at disrupting nuclear foci in a cell based assay, using high content imaging to visualise the number, size and intensity of foci we initially discovered that PNA and 2’OMe, were seemingly taken up via gymnosis by DM1 cells, and removed nuclear foci at nanomolar concentrations. However further experimentation using live cell imaging indicated that although all CMOs could enter the cell, in all disease models tested, via gymnosis, the CMOs could not penetrate the nuclear membrane. In depth analysis led us to identify an artefact of the in-situ process used to identify these foci, explaining earlier positive results. As the target mRNA is trapped within the nuclear compartment we investigated several transfection reagents for their ability to deliver 2’OMe oligonucleotides to the nucleus using live cell fluorescent imaging and a modified northern blot based method. It was established that polyethylenimine could successfully deliver 2’OMe oligonucleotides to the cell, with a high abundance of the oligonucleotide residing within the nuclear compartment. It was observed that PEI degrades the expanded nuclear retained repeat in the DMPK transcript of a DM1 patient cell line alone, without the addition of an antisense agent, in a concentration dependent manner.